Transesophageal Echocardiography in Ischemic Stroke With Atrial Fibrillation - Kanta Tanaka; Masatoshi Koga; Keon‐Joo Lee; Beom Joon Kim; Tadataka Mizoguchi; Eun Lyeong Park; Juneyoung Lee; Sohei Yoshimura; Jae‐Kwan Cha; Byung‐Chul Lee; Junpei Koge; Hee‐Joon Bae; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2021)
Background To clarify differences in clinical significance of intracardiac thrombi in nonvalvular atrial fibrillation‐associated stroke as identified by transesophageal echocardiography (TEE) and transthoracic echocardiography (TTE). Methods and Results Using patient data on nonvalvular atrial fibrillation‐associated ischemic stroke between 2011 and 2014 from 15 South Korean stroke centers (n=4841) and 18 Japanese centers (n=1192), implementation rates of TEE/TTE, and detection rates of intracardiac thrombi at each center were correlated. The primary outcome was recurrent ischemic stroke at 1 year after the onset. A total of 5648 patients (median age, 75 years; 2650 women) were analyzed. Intracardiac thrombi were detected in 75 patients (1.3%) overall. Thrombi were detected in 7.8% of patients with TEE (either TEE alone or TEE+TTE: n=679) and in 0.6% of those with TTE alone (n=3572). Thrombus detection rates varied between 0% and 14.3% among centers. As TEE implementation rates at each center increased from 0% to 56.7%, thrombus detection rates increased linearly (detection rate [%]=0.11×TEE rate [%]+1.09 [linear regression], P<0.01). TTE implementation rates (32.3%–100%) were not associated with thrombus detection rates (P=0.53). Intracardiac thrombi were associated with risk of recurrent ischemic stroke overall (adjusted hazard ratio [aHR] 2.35, 95% CI, 1.07–5.16). Thrombus‐associated ischemic stroke risk was high in patients with TEE (aHR, 3.13; 95% CI, 1.17–8.35), but not in those with TTE alone (aHR, 0.89; 95% CI, 0.12–6.51). Conclusions Our data suggest clinical relevance of TEE for accurate detection and risk stratification of intracardiac thrombi in nonvalvular atrial fibrillation‐associated stroke. Registration URL: https://www.clinicaltrials.gov; Unique identifier: NCT01581502.